Mass open online courses and modern methods of teaching languages - Gotovtseva, I.P.; Sinitsyn, V.Y.; Kashparova, V.S. (Âzyk i tekst, 2017)
The article examines some foreign and Russian mass open online courses (MOOK) that can be used to teach foreign languages in the educational process of higher education institutions, as well as to study foreign languages for the purpose of self-improvement. The possibility of using mass open online courses in the framework of distance and mixed learning models is discussed. В статье рассматриваются некоторые зарубежные и российские массовые открытые онлайн курсы (МООК), которые могут быть использованы для обучения иностранным языкам в учебном процессе высших учебных заведений, а также для изучения иностранных языков с целью самосовершенствования. Обсуждается возможность использования массовых открытых онлайн курсов в рамках дистанционных и смешанных моделей обучения.